Review of the direct thermochemical conversion of lignocellulosic biomass for liquid fuels - Jianchun JIANG,Junming XU,Zhanqian SONG (Frontiers of Agricultural Science and Engineering, 2015)
Increased demand for liquid transportation fuels, environmental concerns and depletion of petroleum resources requires the development of efficient conversion technologies for production of second-generation biofuels from non-food resources. Thermochemical approaches hold great potential for conversion of lignocellulosic biomass into liquid fuels. Direct thermochemical processes convert biomass into liquid fuels in one step using heat and catalysts and have many advantages over indirect and biological processes, such as greater feedstock flexibility, integrated conversion of whole biomass, and lower operation costs. Several direct thermochemical processes are employed in the production of liquid biofuels depending on the nature of the feedstock properties: such as fast pyrolysis/liquefaction of lignocellulosic biomass for bio-oil, including upgrading methods, such as catalytic cracking and hydrogenation. Owing to the substantial amount of liquid fuels consumed by vehicular transport, converting biomass into drop-in liquid fuels may reduce the dependence of the fuel market on petroleum-based fuel products. In this review, we also summarize recent progress in technologies for large-scale equipment for direct thermochemical conversion. We focus on the technical aspects critical to commercialization of the technologies for production of liquid fuels from biomass, including feedstock type, cracking catalysts, catalytic cracking mechanisms, catalytic reactors, and biofuel properties. We also discuss future prospects for direct thermochemical conversion in biorefineries for the production of high grade biofuels.